TRANSFER PRICING, ACCRUALS EARNINGS MANAGEMENT AND CORPORATE TAX AVOIDANCE OF LISTED MULTINATIONAL CORPORATIONS IN NIGERIA (Journal of Global Accounting, 2021)
The study envisages to ascertain the effect of the interaction of transfer pricing and accruals earnings management on corporate tax avoidance of Multinational Corporations (MNCs) in Nigeria. The specific objectives of the study are to ascertain the sensitivity of book-tax differences and effective tax rates to the interaction of discretionary accruals and the transfer price index of multinational firms. The study adopts the ex post facto research design. The sample was restricted to 50 Multinational Corporations (MNCs) selected using the purposive sampling technique. The data were analysed using the panel Estimated Generalized Least Squares (EGLS)technique, specifically the period random effects specification models. The results showed that the interaction of discretionary accruals and transfer price index negatively affect book-tax differences and effective tax rates. The study concludes thataccruals earnings management and transfer pricingare signifincant determinants of corporate tax avoidance of MNCs in developing ciountires. Based on this, the study recommends that the Government reviews its tax policies to attract more inwards Foreign Direct Investment (FDI) and the Boards of MNCs should be wary of transfer price manipulation as these may be suggestive of managerial opportunistic behaviour for self-seeking actions. Lastly, a critical assessment of the host country peculiarities should be considered by local tax authorities in drafting local regulations..
Keywords: Accruals Earnings Management; Effective Tax Rates; Foreign Direct Investment; Corporate Tax Avoidance; Multinational Corporations; Transfer pricing